Downsizing and flexibility: Recent employment restructuring in Chinese state-owned machinery manufacturing companies - Yongping Chen (Journal for East European Management Studies, 2001)
This paper reports case study research findings on recent employment restructuring practices in the state sector under the transition context of China in the mid-1990s. The research focuses on the drive, process, and outcome of downsizing with respect to labour flexibility in the two state-owned machinery manufacturing companies from the management perspective. By employing the Western downsizing approaches as developed by Cameron.s (1994), empirical findings on downsizing in the two studied Chinese state firms are examined and analyzed. The research concludes that downsizing is a necessary but not sufficient policy. Massively laying off staff does not come without costs. To the contrary it generates new personnel problems such as unwanted quits and drain of human capital that are critical for the continuous business process of the downsizing firm. – – In dieser Arbeit wird von einer Fallstudie berichtet, die sich mit der gegenwärtigen Umstrukturierungspraxis im staatlichen Sektor in China Mitte der 90er Jahre beschäftigt. Aus der Perspektive des Managements und unter Nutzung der von Cameron (1994) entwickelten Downsizing-Ansätzen werden in zwei staatseigenen Maschinenbaubetrieben die Auswirkungen der Verkleinerung auf die Arbeitsflexibilität untersucht. Als Ergebnis wird in der Studie festgestellt, dass die Verkleinerung notwendig, aber nicht ausreichend ist. Insbesondere wird auch auf Probleme im Personalbereich eingegangen.
Keywords: 650